2019
DOI: 10.1007/s11666-019-00938-1
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Corrosion-Resistant Thermal Spray Coatings for Renewable Energy Power Plants. Part I: Effect of Composition and Microstructure

Abstract: Power generation from renewable resources has attracted increasing attention in recent years owing to the global implementation of clean energy policies. However, such power plants suffer from severe high-temperature corrosion of critical components such as water walls and superheater tubes. The corrosion is mainly triggered by aggressive gases like HCl, H 2 O, etc., often in combination with alkali and metal chlorides that are produced during fuel combustion. Employment of a dense defect-free adherent coating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(28 citation statements)
references
References 186 publications
0
27
0
1
Order By: Relevance
“…The biomass components include cellulose, hemicellulose, lignin, water, small amounts of lipids, proteins, monosaccharides, starches, hydrocarbons, ash, and other ingredients. These components produce chlorides, sulfates, polysulfates, and sulfides after combustion, leading to the corrosion of metals and metal oxides in the boiler [20]. Vassilev et al [11] reported that kinds of biomass have similar composition and a little difference between the mass.…”
Section: Biomass Compositionmentioning
confidence: 99%
“…The biomass components include cellulose, hemicellulose, lignin, water, small amounts of lipids, proteins, monosaccharides, starches, hydrocarbons, ash, and other ingredients. These components produce chlorides, sulfates, polysulfates, and sulfides after combustion, leading to the corrosion of metals and metal oxides in the boiler [20]. Vassilev et al [11] reported that kinds of biomass have similar composition and a little difference between the mass.…”
Section: Biomass Compositionmentioning
confidence: 99%
“…The deposition method of anti-corrosive coatings is a crucial factor in determining the surface morphology. Coatings are usually produced by spin casting [38][39][40], molecularlayer deposition (MLD) [41,42], vapor-deposition polymerization (VDP) [43,44], or spray coating techniques [45,46]. These methods adopt a layer-by-layer deposition approach, and each layer adheres to each other rapidly, hindering the crosslinking of polymer chains and resulting in cracks and low strength [47][48][49][50].…”
Section: Introductionmentioning
confidence: 99%
“…Surfacing with hard wear-resistant materials [Kartsev 2020] is intended to increase the wear resistance of sealing, rubbing, and other surfaces of parts operating under conditions of metal-to-metal friction in corrosive media (acid, alkali, salt, and organic solvent) [Panda 2014[Panda , 2018a[Panda ,b, 2019Valicek 2016& 2017, Macala 2009& 2017, Pandova 2018, Krenicky 2012, high and low temperatures, and/or pressure [Bozek 2021]. The research [Sadeghi 2019] includes a substantive discussion of high-temperature corrosion mechanisms, new coating formulations, and a brief comparison of corrosion-resistant coatings obtained using various thermal surfacing techniques. It is suggested that with a careful and reasonable choice of technique and technology of surfacing, as well as compliance with a certain temperature range of pre-and associated heating of parts, it will be possible to obtain a high-quality connection of wear-resistant layers of alloys based on iron, nickel or cobalt [Miglierini 2004, Babinets 2020, Pollak 2020a.…”
Section: Introductionmentioning
confidence: 99%